Hvad Abram så: 1 Mos 15 som apokalyptisk tekst - Due, Mads (Dansk Teologisk Tidsskrift, 2025)
This study analyses the vision of Abram in Gen 15 based on insights from apocalyptic literature found in the Old Testament and Pseudepigrapha. The kind of visionary event experienced by Abram is usu-ally found in prophetic literature, but even more often in apocalypses (e.g., Dan 7-12). Using insights from so-called Prototype Theory, this study argues that the text of Gen 15 might be better understood by appealing to the apocalyptic texts than by appealing to other texts that are normally brought into comparison with it. This means that Gen 15 can be seen as a proto-apocalypse, i.e. one of the literary precursors of an apocalyptic worldview. In short, apocalyptic literature develops the kind of visionary event ascribed to Abram, which reaches its peak in the visions of Daniel and other apocalyptic works.